PERAN YAYASAN AMAL SALEH DALAM MEMBENTUK KARAKTER MAHASISWA - Rizal Safarudin; Zulfamanna Zulfamanna; Sarah Hendrawati; Yulia Sarianti; Fuady Anwar (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
Amal Saleh Foundation is a religious organization managed by students. Students are the future successors of a nation. Students are a benchmark for the sustainability and goodness of a country, the birth of YAS has an important role in shaping the character of students at public colleges, Padang State University, therefore this study aims to explore activities at the Amal Saleh Foundation in Shaping Student Character. This study uses a qualitative method with a case study approach (case study design). Data sources were taken from twenty informants through in-depth interviews. The informant is an active student of the General College of Padang State University and is also a Santri of the Amal Saleh Foundation. Data collection techniques used are interviews, observation and documentation studies. All interview results were then analyzed Thematically using the Nvivo12 qualitative analysis software. Overall the results of the analysis show that there are four activities at the Amal Saleh Foundation in Shaping Student Character, namely: i) Ta'lim, ii) Tahsin, iii) Sunday morning lectures and iv) Safari Ramadhan. The results of this study have also proven that Amal Saleh Foundation is successful and has an important role in producing students with character.